Building maintenance policy for office high rise buildings in Malaysia: A preliminary study in Klang valley - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (2011)
Large high rise building is relatively complicated in maintenance. The value of buildings depends on the quality, safety and service of the maintenance policy standard provided and implemented in them. Building maintenance policy standard involves obtaining maximum benefit from the investment made on the maintenance activities. This paper presents the preliminary finding of a study on the building maintenance policy standard of selected large high rise buildings in Klang Valley, Malaysia. Seven office high rise buildings were investigated. Information on maintenance policy, including the type of maintenance conducted, the existence policy and budget, is collected through unstructured interviews. Maintenance in buildings in Malaysia is on the increase regardless of size, type, location, and ownership. The current maintenance policy procedures in Malaysia are however based on house rule and contract agreement. The weaknesses in the current procedures are the primary problems because they do not explicitly link maintenance needs with building performance with respect to the building users. The building users measure the performance of a building with various criteria. The condition of a building is just one of those criteria. This research establishes the need for a building maintenance policy that is based on the concept of building’s value in the effort to lead towards the optimization of building maintenance system. Maintenance policy standard that is value based allows users to be proactively put at the centre of maintenance management during decision making processes and takes into consideration both the objective and subjective requirements of users. The paper concludes that a clear maintenance policy does not exist yet in the maintenance of high rise buildings.